Evaluasi sifat fisik serbuk kulit nanas (Ananas comosus L. Merr.) sebagai jamu ternak antiparamphistomiasis: Physical characteristic evaluation of pineapple (Ananas comosus L. Merr.) rind powder for livestock’s jamu for antiparamphistomiasis - Andhia Rosyantari; Nabila Dewi; Surya Febrianto; Iman Pratama (Fakultas Peternakan Universitas Papua, 2022)
Abstract Based on empirical use and scientific studies, pineapple peel extract has antiparamphistomiasis activity. Pineapple peel has the potential to be developed as a veterinary dosage form in the form of jamu ternak. The aim of the study is to evaluate the physical characteristics of pineapple peel powder compared to standard parameters. The test consists of the organoleptic test, pH test, visual uniformity, weight uniformity, water content determination, flowability, and degree of fineness. The prepared pineapple peel juice was freeze-dried to obtain a powder. The result revealed that the yield of freeze-drying pineapple powder was 15,30%. The pineapple peel powder’s organoleptic properties were as follows: Yellow colour, distinctive aroma of pineapple, and sour taste, the value of pH test is 4,376±0,03, the degree of fineness of the powder is classified as fine, the average of weight uniformity is 0,398±0,00374, and water content is 4,547%±0,008. According to compressibility Index and Hausner ratio was confirming good flow properties. The study suggests that pineapple peel powder could be developed as an ethnoveterinary preparation. Keywords: Antiparamphistomiasis; Livestock’s jamu; Physicochemical evaluation; Pineapple peel powder Abstrak Ekstrak air kulit nanas berkhasiat sebagai antiparamphistomiasis berdasarkan penggunaan secara empiris dan studi saintifik. Berdasarkan potensi tersebut perlu dikembangkan sediaan obat hewan yang terstandar. Penelitian ini bertujuan mengevaluasi sifat fisik serbuk ekstrak kulit nanas sebagai jamu ternak antiparamphistomiasis berdasarkan parameter standar. Uji yang dilakukan berupa uji organoleptik, pH, derajat halus, keseragaman bobot, kadar air, keseragaman tampilan dan sifat alir. Serbuk kulit nanas diperoleh dengan metode kering beku. Hasil rendemen serbuk sebesar 15,30%. Serbuk kulit nanas memiliki warna kuning pucat, bau harum aromatik dan rasa mais sedikit kecut khas nanas. pH sediaan serbuk yaitu 4,376±0,03, derajat halus serbuk tergolong halus, bobot serbuk sebesar 0,398g±0,00374, kadar air 4,547%±0,008, serbuk seragam dengan sifat alir sangat baik. berdasarkan hasil yang diperoleh serbuk kulit nanas memiliki kriteria sediaan serbuk yang baik berdasarkan parameter evlausi sediaan, oleh karena itu berpotensi dikembangkan sebagai sediaan etnoveteriner. Kata kunci: Antiparamphistomiasis; Evaluasi sediaan; Jamu ternak; Serbuk kulit nanas